Oil palm workers: designing ergonomics harvesting tool using user centered design approach to reducing awkward body posture by CATIA simulation - Mohd Yusoff, Irwan Syah; Mohd Tamrin, Shamsul Bahri; Mat Said, Aini; Ng, Yee Guan; Ippei, Mori (Tehran University of Medical Sciences, 2014)
Background: The aim of this study is to develop a new ergonomics chisel based on user centered design approach and to evaluate the effectiveness for reducing awkward posture using CATIA software for simulation analysis. Methods: Respondents were selected using purposive sampling – age 18 – 49 years old, men, experience using chisel (>1 month). A set of questionnaire were used to interview workers while postural risks were determined using Rapid Upper Limb Assessment (RULA). Selected anthropometric parameters were taken and user centered design concept were applied to determine mismatch and to facilitate design process. CATIA software was used to integrate the results of postural analysis and anthropometric measurement using 3D modeling. Results: A total of 273 male harvesters participated in this study. The result shows 5.2% of the chisels’ length of handles matches with the respondents whereas none (100%) of the chisels’ circumference of handle matches with respondents’ internal grip diameter. Tool-chisel usage, majority of harvester bend forward while harvesting (96.7%) and most of workers having blister (83.2%), redness (85.3%) and numbness (65.9%) during harvesting. RULA simulation analysis showed the score action level for new design is 3(further investigated need and changes may be required) compared to existing tool are in action score 7(investigated and changes required immediately). Conclusions: The study showed that the design of new harvesting tool has the potential to reduce awkward body posture during harvesting activities as compared to existing tools.